A escola em tempo integral e o currículo Potiguar para o ensino médio: perspectivas a partir da visão de docentes da geografia - Cunha, João Paulo Medeiros da (2023)
The demand for quality public education to address Brazilian educational failures intensified in the last decade of the 20th century, leading to the development of educational policies influenced by a global agenda led by major international organizations and private sector involvement, viewing public education as a profitable venture. In this context, integral education emerged, becoming part of Brazilian legislation and mentioned for the first time in Law 9,394/96, subsequently included in the National Education Plan (PNE) 2001-2010 and PNE 2014-2024. It gained strength with Measure Provision No. 746, establishing the Policy for Strengthening the Implementation of Full-Time High Schools, sanctioned by Law No. 13,415 on February 16, 2017. This initiative accelerated the implementation of Full-Time Education in some states, with the focus of this study being the state of Rio Grande do Norte, which aligned with the Comprehensive Education policy for High School through its State Education Plan. Given this, there was a need to monitor and analyze how full-time education would be integrated into the New High School curriculum. The overall objective is to analyze the implementation process of full-time education and the curriculum from the perspectives of Geography teachers in state high schools in Natal, RN. Three specific objectives were delineated: list historical experiences of full-time education in Brazil, analyze the changes this model and the full-time curriculum bring to teachers' work routines, and identify how implementation affects Geography teachers' practices in Elective Components. To achieve these objectives, the research relied on a qualitative approach for data generation and interpretation, using semi-structured interviews and direct observation as instruments. Documentary research was also conducted at certain stages. In conclusion, this work justifies its contribution to understanding the implementation of full-time education in public schools in RN, valuing the perspectives of Geography teachers. It is evident that full-time teaching has not been tailored to the Brazilian reality and existing obstacles, overlooking school infrastructure issues, precarious and controlled work conditions, increased workload for teachers, and poor quality or lack of teacher training. Additionally, there seems to be an attempt to further diminish the cultural capital of the working class, maintaining subservience, as evidenced by the lack of interest in citizen education based on scientific knowledge and critical thinking.